Analisis Yuridis Peraturan Penjagaan Lembaga Pemasyarakatan Terkait dengan Gangguan Keamanan dan Ketertiban di Lembaga Pemasyarakatan Klas IIb Lubuk Pakam - Sembiring, Loviga Ferdinanta; Barus, Utary Maharani; Isnaini, Isnaini (ARBITER: Jurnal Ilmiah Magister Hukum, 2019)
The purpose of this study is to find out 1) whether the legal protection carried out by prison officers for prisoners is in accordance with Law Number 12 of 1999 concerning Corrections; 2) how is the security system at Class II B Penitentiary in Lubuk Pakam; and 3) What are the obstacles faced in law enforcement in Class II B Penitentiary, Lubuk Pakam. The research method used in this study is empirical normative juridical supported by secondary data and interviews with informants. The results of the study show that: 1) Correctional Institutions are a place to carry out the formation of prisoners and correctional students. 2) Community service and security and order maintenance in Lapas are not yet optimal, the quality of human security officers is low, and 3) Development officers and administrative officers must always be consolidated through coaching officers with concurrent and special meetings/briefings.